Test-Retest Reliability of the Short-Form Survivor Unmet Needs Survey - Karen Taylor; Max Bulsara; Leanne Monterosso (Elsevier, 2018)
Objective: Reliable and valid needs assessment measures are important assessment tools in cancer survivorship care. A new 30-item short-form version of the Survivor Unmet Needs Survey (SF-SUNS) was developed and validated with cancer survivors, including hematology cancer survivors; however, test-retest reliability has not been established. The objective of this study was to assess the test-retest reliability of the SF-SUNS with a cohort of lymphoma survivors (n = 40). Methods: Test-retest reliability of the SF-SUNS was conducted at two time points: baseline (time 1) and 5 days later (time 2). Test-retest data were collected from lymphoma cancer survivors (n = 40) in a large tertiary cancer center in Western Australia. Intraclass correlation analyses compared data at time 1 (baseline) and time 2 (5 days later). Cronbach's alpha analyses were performed to assess the internal consistency at both time points. Results: The majority (23/30, 77%) of items achieved test-retest reliability scores 0.45-0.74 (fair to good). A high degree of overall internal consistency was demonstrated (time 1 = 0.92, time 2 = 0.95), with scores 0.65-0.94 across subscales for both time points. Conclusions: Mixed test-retest reliability of the SF-SUNS was established. Our results indicate the SF-SUNS is responsive to the changing needs of lymphoma cancer survivors. Routine use of cancer survivorship specific needs-based assessments is required in oncology care today. Nurses are well placed to administer these assessments and provide tailored information and resources. Further assessment of test-retest reliability in hematology and other cancer cohorts is warranted.